SENI SPIRITUAL DALAM KONSEPSI ESTETIKA SEYYED HOSSEIN NASR - M. Farkhan M (CMES (Center of Middle Eastern Studies), 2013)
This article describes a method of spiritual dimension in understanding the nature ofart. One of the ideas that emerged in the art world is the idea of the spiritual artconceived by Seyyed Hossein Nasr. Art is a spiritual view of creativity that once a form ofart presupposes that actually has the dimensions or viewpoints that are not one-sided buttwo-way, i.e. physical viewpoint or exoteric and esoteric spiritual viewpoint.   This study was conducted based on the hermeneutic readings to the texts of religiousthought. The purpose is to find an aesthetic view of the artwork that builds upon religiousvalues and how spiritual art form in the light of faith is placed in human life maqamamong other arts. Spiritual art is not a choice but something that exists, which should beread through physical knowledge that real empirical.